2016
DOI: 10.1097/scs.0000000000002856
|View full text |Cite
|
Sign up to set email alerts
|

A Reduction Technique for a Depressed and Impacted Nasomaxillary Buttress Fracture

Abstract: The aim of this study is to introduce an easy method of reducing the depressed and impacted segment in a nasomaxillary buttress fracture.Through the gingiva-labial vestibular incision, the fracture segments were exposed. A blunt end of the Cottle elevator was inserted to the cleft of the fracture segments. An upward and lateral force was applied until the impacted segment was released and reduced to its anatomical position. Then, the segments were fixed with a miniplate.Fifteen patients (12 males, 3 females, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…However, a 2012 study distinguished nasomaxillary fractures from NOE fractures based on the presence of medial canthal tendon avulsion with canthal dystopia only in the latter [9]. A new surgical technique for managing nasomaxillary fractures was described in 2016 [2]. In the AOCMF classification system for midface fracture, a left nasomaxillary fracture is coded: 92 U.I.L [10,11] but it must be specified there is no medial canthal tendon avulsion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, a 2012 study distinguished nasomaxillary fractures from NOE fractures based on the presence of medial canthal tendon avulsion with canthal dystopia only in the latter [9]. A new surgical technique for managing nasomaxillary fractures was described in 2016 [2]. In the AOCMF classification system for midface fracture, a left nasomaxillary fracture is coded: 92 U.I.L [10,11] but it must be specified there is no medial canthal tendon avulsion.…”
Section: Discussionmentioning
confidence: 99%
“…Non-operative treatment by endonasal reduction and nasal meshes has been reported [2,6] but may carry a high risk of residual cosmetic and functional impairments. More specifically, insufficient reduction by the endonasal manoeuvres may be followed by nasal obstruction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgical treatment of medial maxillary (nasolabial buttress) fractures requires an accurate diagnosis and careful planning in each case because the treatment of concomitant fractures is also necessary. Recently, Yoshioka et al [ 2 ] and Hwang et al [ 3 ] have only reported 8 and 15 cases of this fracture, respectively. Medial maxillary (nasomaxillary) fractures are not included in any current classification of the maxillary fracture patterns, which include Le Fort-type, sagittal, or fracture of the alveolar process.…”
Section: Introductionmentioning
confidence: 99%